Klasifikasi Menggunakan Metode Naïve Bayes: Tingkat Pengaruh Penggunaan Gadget terhadap Kematangan Kecerdasan Emosi Mahasiswa - Umar Zaky; Ari Prasetyoaji; Ilham Fathullah (JUSIFO : Jurnal Sistem Informasi, 2020)
Gadgets are generally used by individuals to help increase their knowledge, facilitate communication, and also accelerate the development of scientific information. The use of gadgets such as smartphones, laptops, tablets, or iPads has become a habit among students. The students use gadgets for their daily needs. The convenience offered by using gadgets makes students need to be wise in using gadgets. The students can easily search for the lecture materials, take online classes, communicate in a virtual classroom, and see the results of their studies. However, gadgets also have a negative side. Some of the negative effects of the use of gadgets, such as addiction to playing online games, reduced face-to-face interaction, cheating on exams. This article aims to build a classification application for the level of influence of gadget use on the maturity of students' emotional intelligence using the Naïve Bayes method. From this research, the classification application for the level of influence of gadget use on the maturity of student's emotional intelligence using the Naïve Bayes method has been created. The test results of this application show an accuracy of 82%.